2018
DOI: 10.1016/j.scitotenv.2018.06.278
|View full text |Cite
|
Sign up to set email alerts
|

Elevated nutrient concentrations in headwaters affected by drained peatland

Abstract: Nutrient export from drained peatland has significant impacts on aquatic environments in Nordic catchments. Spatial information on variations in nutrient concentrations across different landscapes and land uses is needed to design measures for achieving the good ecological status of the EU Water Framework Directive. In this study we determined background concentrations in natural peatland-dominated streams and examined effects of peatland use practices on water quality in headwater catchments. We quantified so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 40 publications
6
13
0
Order By: Relevance
“…Extensive peatland areas throughout Fennoscandia have been drained, in more or less systematic ways, with the purpose to improve forest production (Päivänen and Hånell 2012;Sikström and Hökkä 2016). Area drained for peatland forestry has been positively correlated with TOC and DOC (Marttila et al 2018) and drained peatland forests have been shown to be significantly greater sources of DOC to receiving waters than undrained peatlands and upland forest soils (Rantakari et al 2010). Päivänen and Hånell (2012) suggested that in drained peatlands, aeration promotes microbial processes and solubility, and thereby increases peat mineralization, resulting in the increasing DOC concentration.…”
Section: Manipulating Hydrological Connectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive peatland areas throughout Fennoscandia have been drained, in more or less systematic ways, with the purpose to improve forest production (Päivänen and Hånell 2012;Sikström and Hökkä 2016). Area drained for peatland forestry has been positively correlated with TOC and DOC (Marttila et al 2018) and drained peatland forests have been shown to be significantly greater sources of DOC to receiving waters than undrained peatlands and upland forest soils (Rantakari et al 2010). Päivänen and Hånell (2012) suggested that in drained peatlands, aeration promotes microbial processes and solubility, and thereby increases peat mineralization, resulting in the increasing DOC concentration.…”
Section: Manipulating Hydrological Connectivitymentioning
confidence: 99%
“…Päivänen and Hånell (2012) suggested that in drained peatlands, aeration promotes microbial processes and solubility, and thereby increases peat mineralization, resulting in the increasing DOC concentration. This increase in peat decomposition level due to drainage, combined with naturally fluctuating water tables, creates a condition with increased loads of DOC and nutrients from drained peatlands (Marttila et al 2018;Nieminen et al 2018).…”
Section: Manipulating Hydrological Connectivitymentioning
confidence: 99%
“…However, a recent study [21] suggested that N and P concentrations in runoff from old drained peatlands may slowly increase as a function of time. Drainage causes also long-term changes in the quality of organic matter in runoff [22]. There is a clear knowledge gap between the controlled paired catchment studies and monitoring studies concerning response of water quality to long-term effects of drainage and low intensity harvesting such as thinning, small area clear-cutting and partial harvesting.…”
Section: Introductionmentioning
confidence: 99%
“…Local increases of nitrogen and phosphorus concentrations in forestry‐impacted catchments is well‐documented (De Wit et al, 2014; Lofgren, Ring, von Bromssen, Sorensen, & Hogbom, 2009) but its impact on a wider temporal and spatial scale is less clear (Sponseller et al, 2016). In areas with intensive peatland forestry like Finland, harvesting operations in forest on organic soils are of specific concern (Marttila et al, 2018; Nieminen et al, 2018). Furthermore, intensified forestry by conducting whole tree harvesting may require application of a fertilizer to avoid reduced forest growth (Akselsson, Westling, Sverdrup, & Gundersen, 2007; Merila et al, 2014).…”
Section: Introductionmentioning
confidence: 99%